Seasonal variation in the behaviour of a short-lived rodent - Eccard, Jana (Prof. Dr.); Herde, Antje (2017)
Background: Short lived, iteroparous animals in seasonal environments experience variable social and environmental conditions over their lifetime. Animals can be divided into those with a "young-of-the-year" life history (YY, reproducing and dying in the summer of birth) and an "overwinter" life history (OW, overwintering in a subadult state before reproducing next spring). We investigated how behavioural patterns across the population were affected by season and sex, and whether variation in behaviour reflects the variation in life history patterns of each season. Applications of pace-of-life (POL) theory would suggest that long-lived OW animals are shyer in order to increase survival, and YY are bolder in order to increase reproduction. Therefore, we expected that in winter and spring samples, when only OW can be sampled, the animals should be shyer than in summer and autumn, when both OW and YY animals can be sampled. We studied common vole (Microtus arvalis) populations, which express typical, intra-annual density fluctuation. We captured a total of 492 voles at different months over 3 years and examined boldness and activity level with two standardised behavioural experiments. Results: Behavioural variables of the two tests were correlated with each other. Boldness, measured as short latencies in both tests, was extremely high in spring compared to other seasons. Activity level was highest in spring and summer, and higher in males than in females. Conclusion: Being bold in laboratory tests may translate into higher risk-taking in nature by being more mobile while seeking out partners or valuable territories. Possible explanations include asset-protection, with OW animals being rather old with low residual reproductive value in spring. Therefore, OW may take higher risks during this season. Offspring born in spring encounter a lower population density and may have higher reproductive value than offspring of later cohorts. A constant connection between life history and animal personality, as suggested by the ...